2018
DOI: 10.3892/mmr.2018.8597
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dexmedetomidine post‑treatment on BDNF and VEGF expression following cerebral ischemia/reperfusion injury in rats

Abstract: Brain‑derived neurotrophic factor (BDNF) and vascular endothelial growth factor (VEGF) serves a significant role in neural protection by activating the phosphatidylinositol 3‑kinase (PI3K)/Akt signaling pathway, which also was associated with the neuroprotective the treatment with dexmedetomidine (DEX). The present study aimed to further explore whether treatment with DEX post‑IR increased the expression level of BDNF and VEGF in the rat brain. A total of 30 healthy, clean male Wistar rats were randomly divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
3
14
0
Order By: Relevance
“…Postoperative reductions in serum brain‐derived neurotrophic factors were associated with cognitive dysfunction, which suggests reductions in cerebral concentrations 15,32. Dexmedetomidine increases cerebral brain‐derived neurotrophic factor concentrations and associated neuroprotective effects 33,34. Dexmedetomidine can reverse anaesthesia‐induced reductions in plasma concentrations within 24 postoperative hours 35.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative reductions in serum brain‐derived neurotrophic factors were associated with cognitive dysfunction, which suggests reductions in cerebral concentrations 15,32. Dexmedetomidine increases cerebral brain‐derived neurotrophic factor concentrations and associated neuroprotective effects 33,34. Dexmedetomidine can reverse anaesthesia‐induced reductions in plasma concentrations within 24 postoperative hours 35.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a study in an IR injury in rats, found that post-surgical treatment with dexmedetomidine may increase the expression of VEGF 34 and also studies showing that calcitriol increases VEGF expression and release in vascular smooth muscle cells 35,36 , which may have the role in increasing flap viability and support our findings. However, in our study, we have evaluated the oxidative mechanisms and assessed the angiogenesis morphologically in flap viability other than focusing on neovascular angiogenesis, tissue regeneration, or hypoxia with specific biomarkers such as VEGF, transforming growth factor beta (TGF-beta), and hypoxia inducible factor 1 (HIF-1); we think that studying these biomarkers definitely warrants a further study to confirm our results.…”
Section: ■ Discussionsupporting
confidence: 88%
“…Brain‐derived neurotrophic factor (BDNF) plays a pivotal role in neural development and diseases (Binder & Scharfman, 2004). It was reported that BDNF mRNA expression was higher in the I/R model in vivo from 6 hr to 3 days post‐I/R surgery (Li et al., 2018). Here, we examined that AG490 treatment further enhanced the expression of BDNF not only in the serum but also in the brain.…”
Section: Discussionmentioning
confidence: 99%